Adverse Impact of HIV-1 on Long-term Outcomes Following HCV DAA Treatment: Final Results of ACTG A5320, the Viral Hepatitis C Infection Long-term Cohort Study (VHICS). (6th March 2023) - Wyles, David L; Kang, Minhee; Matining, Roy M; Murphy, Robert L; Peters, Marion G
Abstract: Background: Long-term outcome data after hepatitis C virus (HCV) treatment are limited, particularly for comparisons between persons with and without HIV. Methods: A5320 was a prospective cohort study that enrolled participants within 12 months of completing HCV DAA therapy, with or without sustained virologic response (SVR). The primary end point was composite: time to death or development of a targeted diagnosis. Component outcomes (death and targeted diagnosis) and liver-related events were also analyzed. The effects of HIV serostatus, HIV RNA and CD4, and liver disease stage on the outcomes were assessed. Follow-up was designated for 5 years. Results: Three hundred thirty-two participants enrolled: 184 with HIV/HCV (130 SVR) and 148 with HCV (125 SVR). The primary analysis was dominated by targeted diagnoses. Increased rates of targeted diagnoses were seen in HCV-HIV/SVR compared with HCV/SVR ( P = .016), with an incidence rate of 6.7 and 3.4 per 100 person-years, respectively. Among persons without HIV, higher rates of targeted diagnoses were observed in non-SVRs ( P = .007), 10.8 vs 3.4/100 person-years. No significant difference was seen by SVR status among those with HIV. There were 15 deaths; all liver-related deaths (n = 4) occurred in non-SVR groups. Conclusions: HCV cure following therapy reduces subsequent development of new clinical events, supporting the use of SVR as a predictor for clinical outcomes. Despite HIV control, a significant decrease in incident events or mortality was not demonstrated for people with HIV who achieved SVR, suggesting that coinfection attenuates the beneficial impact of SVR. Research is needed to better define mechanisms accounting for the long-term negative impact of controlled HIV infection. Abstract : Limited prospective data are available after HCV DAA therapy, particularly in persons with HIV. Results from A5320 demonstrate worse long-term clinical outcomes after successful HCV therapy in PWH compared to a contemporaneously enrolled group without HIV.